1982
DOI: 10.1128/aem.44.3.757-760.1982
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic biotransformations of 2,4,6-trinitrotoluene under simulated composting conditions

Abstract: The biotransformations of 14C-labeled 2,4,6-trinitrotoluene by thermophilic microorganisms in a compost system were determined. The reduction products identified in solvent extracts were similar to those identified in mesophilic systems. A significant percentage of the 14C-labeled products were bound to humus fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0
2

Year Published

1993
1993
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(89 citation statements)
references
References 7 publications
4
83
0
2
Order By: Relevance
“…The kinetics of these reduction pathways are complex and determination of rates of formation and reaction of individual products would be difficult. A laboratory composting study concluded that reduction is favored in the para position [6].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The kinetics of these reduction pathways are complex and determination of rates of formation and reaction of individual products would be difficult. A laboratory composting study concluded that reduction is favored in the para position [6].…”
Section: Discussionmentioning
confidence: 97%
“…The increases in the concentrations of the extractable TNT metabolites did not quantitatively account for the decreases in TNT concentrations because they were only transient intermediates in the biotransformation of TNT [6]. The final products of the TNT and other explosives were not observed by the HPLC method, and their fate is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also observed (unpublished data) the decrease of TNT and the accumulation of monoamino-, diamino-, and azoxydimer metabolites after storing leachates from other composts for about 4 months at 4°C. The azoxydimers are thought to be derived from hydroxyamines that also are precursors to the monoamino derivatives [ 5 ] . The formation of the dimers, although transitory in their accumulation, probably is facilitated in the aqueous solution conditions of leaching.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial principles underlying the operation of these systems have been reviewed by others [1]. Bioremediation technologies include soil slurry reactors [2][3][4][5], composting [6][7][8], and land farming. Bioremediation technologies can be significantly less expensive but trade off cost for the time required to reach selected end-point concentrations.…”
Section: Introductionmentioning
confidence: 99%